2022
DOI: 10.3390/foods11081154
|View full text |Cite
|
Sign up to set email alerts
|

Quality Multiverse of Beef and Pork Meat in a Single Score

Abstract: The rationale behind this review is the potential of developing a single score tool for meat quality evaluation based on visual and sensorial assessments of fresh meat. Based on the known sensory wheel concept, the first step was to create quality wheels capturing most common intrinsic and extrinsic quality cues of pork and beef outlined in the latest scientific papers. This resulted in identifying meat color, sensory characteristics and fat content as the most important intrinsic quality cues of fresh beef an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…e research outcome demonstrated that level of paprika powder used in this study was high enough to prevail over the effect of nitrites on the colour of kulen. e two most common analytical methods to measure colour of food samples are traditional colorimeter and CVS [29]. Recently, the study by Tomasevic et al [22] revealed that traditional colorimeters might not be a suitable technique for measuring the colour of bi-coloured meat products like fermented sausages because the aperture size of most colorimeters is too big to measure the colour of meat and fat segments separately.…”
Section: Colourmentioning
confidence: 99%
“…e research outcome demonstrated that level of paprika powder used in this study was high enough to prevail over the effect of nitrites on the colour of kulen. e two most common analytical methods to measure colour of food samples are traditional colorimeter and CVS [29]. Recently, the study by Tomasevic et al [22] revealed that traditional colorimeters might not be a suitable technique for measuring the colour of bi-coloured meat products like fermented sausages because the aperture size of most colorimeters is too big to measure the colour of meat and fat segments separately.…”
Section: Colourmentioning
confidence: 99%
“…In order to understand the oral processing parameters associated with meat, it is necessary to look at its main quality characteristics such as sensory attributes or meat texture from a different perspective. These intrinsic quality cues have been revealed by (Rajic et al, 2022) in their literature review of pork and beef meat. When a sufficient number of panellists is used in food oral processing studies, clear correlations between instrumental texture and some mastication parameters and even saliva incorporation may be revealed (Ilić et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, consumers consider various quality characteristics when buying and consuming meat. Consumers evaluate the intrinsic quality cues of meat and meat products, which are colour, taste, freshness, fat content, textures, nutritional value and others (de Araújo et al, 2022;Rajic et al, 2022). According to Gondeková et al (2020) consumers are influenced by meat colour, which is perceived as key quality attribute.…”
Section: Article Infomentioning
confidence: 99%